Chemistry: an introduction to general, organic, and biological chemistry - Karen C. Timberlake (Pearson, 2006)
Berisi : Chapter Guide, Learning Goals, Tutorials, Review Questions, Quizzes, Career Focus, Case Studies, PowerPoint Presentations, Math Review, Interact Math, Research Navigator, Flashcards, Periodic Table, Calculator, Glossary. Dalam bentuk teks.